The impact of informant gender on children's endorsement of scientific and non‐scientific information. (14th October 2021) - Rackoff, Gavin N.; Lagoni, Daniel W.; Shoshany, Mia F.; Moursi, Nasreen A.; Hennefield, Laura
Abstract : By roughly 6 years of age, children acquire the stereotype that men are more competent than women in science, technology, engineering, and mathematics (STEM), potentially leading to greater trust in scientific information provided by men. This study tested whether 3‐ to 8‐year‐old children differentially endorsed conflicting information about science and toys presented by male and female informants depicted as a 'man' and 'woman' (Exp1) or 'scientists' (Exp2). Children were expected to endorse toy testimony from gender‐matched informants; thus, the key question concerned endorsement of science testimony. In Exp1 ( N = 149), boys and girls showed a same‐gender informant preference for toy testimony; however, girls endorsed the male informant's testimony more for science than for toys – but only when tested by a male experimenter. In Exp2 ( N = 264), boys and girls showed a same‐gender preference, irrespective of content. Findings suggest that STEM‐related gender stereotypes might lead girls to trust scientific information presented by men over women in certain contexts.